2011
DOI: 10.1017/s0305000911000171
|View full text |Cite
|
Sign up to set email alerts
|

How to measure the onset of babbling reliably?

Abstract: Various measures for identifying the onset of babbling have been proposed in the literature, but a formal definition of the exact procedure and a thorough validation of the sample size required for reliably establishing babbling onset is lacking. In this paper the reliability of five commonly used measures is assessed using a large longitudinal corpus of spontaneous speech from forty infants (age 0 ; 6-2 ; 0). In a first experiment it is shown that establishing the onset of babbling with reasonable (95%) confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…Even prior research based on laboratory samples has illustrated that infants reported to be in the canonical stage by their parents often fail to meet the .15 criterion (Lewedag, 1995). Factors influencing the ratios that are actually obtained include infant age (infants near 12 months are more likely to meet the criterion than those at nine months for example) and length of sample (in recordings of more than an hour in duration one can target highest periods of volubility, and then the likelihood of exceeding the criterion is higher; Molemans, 2011; Molemans, Van den Berg, Van Severen, & Gillis, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even prior research based on laboratory samples has illustrated that infants reported to be in the canonical stage by their parents often fail to meet the .15 criterion (Lewedag, 1995). Factors influencing the ratios that are actually obtained include infant age (infants near 12 months are more likely to meet the criterion than those at nine months for example) and length of sample (in recordings of more than an hour in duration one can target highest periods of volubility, and then the likelihood of exceeding the criterion is higher; Molemans, 2011; Molemans, Van den Berg, Van Severen, & Gillis, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…However, the value was never presumed to be more than a heuristic—we know that canonical babbling ratios vary substantially based on, for example, sample size (Molemans, Van den Berg, Van Severen, & Gillis, 2011), and there is good reason to believe, based on ongoing research, that it varies based on other factors, such as infant arousal level, and especially on the extent to which infants are engaged in vocal interaction at the time of the sample.…”
Section: Aims and Approachmentioning
confidence: 99%
“…However, new work (Molemans, Van den Berg, Van Severen, & Gillis, 2012) estimates sample-size requirements for reliably determining onset of canonical babbling. For 95% confidence, 300 to 500 utterances were shown to be required, depending on age.…”
Section: Discussionmentioning
confidence: 99%
“…However, resonant productions from low sample sizes can be reasonably identified with relatively small monthly samples (Molemans, Van Den Berg, Severen, & Gillis, 2012) and in this investigation we obtained more hours of videotape for the CAS group than the TYP group to allow for sufficient tokens in the experimental group. The fact that there were substantially more tokens from the TYP group than the experimental group across multiple variables suggested that the token number was sufficient for analysis, and that the results may have underreported any differences between the two groups; but it is also possible that additional recording time from the TYP group would have revealed more ''quiet'' time in this population, reducing apparent differences between the groups.…”
Section: Limitations and Future Research Needsmentioning
confidence: 92%